The Value of Big Endothelin-1 in the Assessment of the Severity of Coronary Artery Calcification. (October 2018) - Wang, Fang; Li, Tiewei; Cong, Xiangfeng; Hou, Zhihui; Lu, Bin; Zhou, Zhou; Chen, Xi
Progression of coronary artery calcification (CAC) was significantly associated with all-cause mortality, and high coronary artery calcium score (CACS) portends a particularly high risk of cardiovascular events. But how often one should rescan is still an unanswered question. Preliminary screening by testing circulating biomarker may be an alternative before repeat computed tomography (CT) scan. The aim of this study was to investigate the value of big endothelin-1 (bigET-1), the precursor of endothelin-1 (ET-1), in predicting the severity of CAC. A total of 428 consecutively patients who performed coronary computed tomography angiography (CCTA) due to chest pain in Fuwai Hospital were included in the study. The clinical characteristics, CACS, and laboratory data were collected, and plasma bigET-1 was detected by enzyme-linked immunosorbent assay (ELISA). The bigET-1 was positively correlated with the CACS ( r = .232, P < .001), and the prevalence of CACS >400 increased significantly in the highest bigET-1 tertile than the lowest tertile. Multivariate analysis showed that bigET-1was the independent predictor of the presence of CACS >400 (odds ratio [OR] = 1.721, 95% confidence interval [CI], 1.002-2.956, P = .049). The receiver operating characteristic (ROC) curve analysis showed that the optimal cutoff value of bigET-1 for predicting CACS >400 was 0.38 pmol/L, with a sensitivity of 59% and specificity of 68% (area under curve [AUC] = 0.65, 95% CI, 0.58-0.72, P < .001). The present study demonstrated that the circulating bigET-1 was valuable in the assessment of the severity of CAC.